The periodisation of Lithuanian history in the context of social history - Alfredas Bumblauskas (Lietuvos Istorijos Studijos, 2006)
The article reviews periodization models of Lithuanian history that are based on the history of politics and culture. A discussion about the periodization of the history of Lithuania is also renewed, and the insights into periodization that are considered to be up-and-coming are given in the article. In the 20th-century historiography of Lithuania, such insights are found in the works of famous historians Z. Ivinskis, J. Jurginis, and E. Gudavičius. Realizing the limitations of the history of politics and culture, attempts are made to formulate the appropriate assumptions for the creation of a periodization model of the development of Lithuanian society on the basis of the insights of the historians mentioned above and on certain theoretical principles of creation of periodization models related to the integral social German history.